A new authentication procedure for client-server applications using HMAC. (4th July 2021) - Shukla, Varun; Misra, Manoj Kumar; Chaturvedi, Atul
Abstract: Hash functions are used for data integrity and authentication but unfortunately they suffer with man in the middle attack problem. An intruder who has command over the communication channel can send an altered message along with its hash and pretends to be the authentic sender. Hash based authentication methods are subject to length based attacks also. So these problems are applicable to all those procedures which involve hash based authentication and routing protocols are one such example because routing protocols use MD5 authentication which is vulnerable in various aspects. So keeping these problems in mind, in this paper, we present a new HMAC implementation method which is a solution of these problems.